HUBUNGAN MOTIVASI KELUARGA DALAM MERAWAT LANSIA YANG MENDERITA HIPERTENSI TERHADAP DERAJAT HIPERTENSI DI PUSKESMAS BUMI AYU - Sussiati " "; Arneliwati " "; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractControl of blood pressure in patients with hypertension in addition to the anti-hypertensive drugs are also required adoption of a healthy lifestyle. Adoption of a healthy lifestyle in elderly need support and motivation from family becomes a support system of the elderly. The study design used is descriptive correlation and cross sectional appproachment. The sample are 78 respondents was purposive sampling. The instrument used are the motivation questionnaire families. The analysis used univariate to determine the frequency distribution and bivariate using chi-square test. The results showed 37 elderly people who have a strong family motivation, as many as 30 older people with mild hypertension degree and the remaining seven older people with moderate degrees of hypertension. The statistic result obtained is ρ-value (0.000) <α (0.05), therefore there is significantly relationship of motivation families in caring for the elderly who suffer from hypertension to the degree of hypertension in Puskesmas Bumi Ayu . The results of this study recommend for health workers, especially nurses to raise awareness of families in motivating caring for the elderly who suffer from hypertension. Keywords: Degree of hypertension, motivation families, elderly